POLITICAL MATTER IN HISTORICAL GOVERNMENT OF TURKIYE’s ELECTION - Muhammet Ebuzer Ersoy (Jurnal Pembaharuan Hukum, 2023)
After two decades in power and more than a dozen elections, Turkey's authoritarian leader Recep Tayyip Erdogan knows how to work a room. At a taxi drivers' convention in Istanbul, they could not get enough of him. He controlled the crowd like the conductor of an orchestra. They cheered and clapped - and booed the opposition - on cue. The venue was a waterside convention centre in Istanbul, built during his time as mayor of the city. The rally reached a crescendo as the president delivered his parting shot: "One Nation, One Flag, One Motherland, One State." This research aims to know the political issue in Turkiye’s election from history of their modern nation and government regulation especially in the voting and choose the president. This study uses a sociological juridical approach, namely research based on normative law (regulations) as well as observing the workings of these regulations in society which make relationship with the political and international issue. The result show President Recep Tayyip Erdogan has won re-election according to the country's Supreme Election Council and unofficial data from the state-run Anadolu Agency. With 100 percent of ballot boxes opened in the run-off, Erdogan has 52.18 percent of the vote, and challenger Kemal Kilicdaroglu has 47.82 percent.